Akuntabilitas Sosial Dalam Peneglolaan Dana Desa (Studi Kasus Di Desa Susukan Kecamatan Susukan Kabupaten Semarang) Universitas Muhammadiyah Surakarta - Ummah, Indah Khuriyati; , Drs. Achmad Muthali'in, M.Si (2016)
This study aimed to describe to describe the management accountability Village Fund in Susukan, Susukan subdistrict, Semarang regency covering , obstacles encountered, and the solutions provided. This study used a qualitative research with case study strategy. Data collected by observation, interview and documentation. Test the validity of the data by triangulation of data sources and data collection techniques. Analysis of the data using interactive analysis techniques through data collection, data reduction, presentation and conclusion. The results showed the village fund management accountability Susukan Susukan District of Semarang District has been done based on the element indicator organized community and capable, responsive governance, compliance culture and context as well as access to information. But in administratively Obstacles still exist it proved with the discrepancy village budget funds for the empowerment of the landfill activities, and coaching youth do not really channeled to the right target. The solution that has been done is PTPKD to make a detailed list and disseminate to the public regarding distribution not budget funds TPA empowerment and youth development.